1980
DOI: 10.1159/000460146
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain in Bonnet and Pigtail Macaques

Abstract: Developmental weight gain was traced in two species of macaque, Macaco radiata and Macaco nemestrina. Some similarities in growth patterns between the two species were observed. Spontaneous obesity in bonnet macaques was observed, and growth curves of these specimens were compared with those of normal animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Obesity has been identified in many primate species, including orangutans, gorillas (1), chimpanzees (2), baboons (Papio ursinus) (3), vervet monkeys (Cercopithecus aethiops) (4), cynomolgus monkeys (Macaca fascicularis) (5), bonnet macaques (Macaca radiata) (6), pigtail macaques (Macaca nemistrina) (7), squirrel monkeys (8), and the Celebes ape (Macaca nigra) (9), although the species most studied is the rhesus monkey (Macaca mulatta) (10)(11)(12). Several rodent species develop a similar adult-onset obesity, including the Sprague-Dawley rat (13), the gerbil (Psammomys obesus, Israeli desert sand rat) (14), the New Zealand Obese mouse, the BSB mouse (Mus spretus and other strains), and the spiny mouse (Acomys caharinus).…”
Section: Obesity As a Disease Of Aging In Primates: The Natural History Of Changes In Body Adipositymentioning
confidence: 99%
“…Obesity has been identified in many primate species, including orangutans, gorillas (1), chimpanzees (2), baboons (Papio ursinus) (3), vervet monkeys (Cercopithecus aethiops) (4), cynomolgus monkeys (Macaca fascicularis) (5), bonnet macaques (Macaca radiata) (6), pigtail macaques (Macaca nemistrina) (7), squirrel monkeys (8), and the Celebes ape (Macaca nigra) (9), although the species most studied is the rhesus monkey (Macaca mulatta) (10)(11)(12). Several rodent species develop a similar adult-onset obesity, including the Sprague-Dawley rat (13), the gerbil (Psammomys obesus, Israeli desert sand rat) (14), the New Zealand Obese mouse, the BSB mouse (Mus spretus and other strains), and the spiny mouse (Acomys caharinus).…”
Section: Obesity As a Disease Of Aging In Primates: The Natural History Of Changes In Body Adipositymentioning
confidence: 99%
“…Local variations or differences in growth patterns among populations within a given species have not been adequately reported. Rosenblum & Smiley (1980) reported a difference between the growth patterns of normal and obese Macaca radiata. The divergence started at 5.5 years of age in females and at 7 years of age in males.…”
Section: Differences Between Sexesmentioning
confidence: 99%
“…Thus, there are no studies that can be compared to the present study. In terms of body weight, Rosenblum and Smiley (1980) gave results for M. nemestrina and M. radiata. Wagenen and Catchpole (1956) reported changes in weights and crown-rump lengths for M. mulatta and Faucheux et al (1978) reported changes in body weight for M. arctoides.…”
Section: Species Differences In Growth Patternsmentioning
confidence: 99%
See 2 more Smart Citations